Elasticity of the flexor carpi ulnaris muscle after an increased number of pitches correlates with increased medial elbow joint space suppression - Saito, A.; Namiki, Y.; Okada, K. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to measure the medial elbow joint space and elasticity of the forearm flexor-pronator muscles in repetitive pitching and to determine which of the forearm flexor-pronator muscles contribute to elbow valgus stability during pitching. Twenty-six collegiate baseball players performed 7 sets of 15 pitches. The medial elbow joint space and elasticity of the pronator teres, flexor carpi radialis, flexor digitorum superficialis (FDS), and flexor carpi ulnaris (FCU) were measured using ultrasonography before pitching and after every 15 pitches. Correlations among the rate of change of these parameters were analyzed using Pearson's correlation coefficients. The medial elbow joint space increased after 60 or more pitches compared with that before pitching (all p < 0.001; effect size [ES]: 0.44-1.22). FDS and FCU elasticity increased after 45 and 60 pitches or more in contrast to that before pitching, respectively (FDS: p = 0.047 and p < 0.001, respectively; ES: 1.05-1.42, FCU: p = 0.011 and p < 0.001, respectively; ES: 1.11-1.48). After 75 or more pitches, the rate of change of FCU elasticity correlated negatively with that of the medial elbow joint space (r = -0.395, r = -0.454, and r = -0.404, after 75, 90, and 105 pitches, respectively). Increased FCU elasticity after repetitive pitching correlated with suppression of the increase of the medial elbow joint space. The FCU may be the primary dynamic stabilizer against the elbow valgus force, and evaluation of the FCU elasticity may be important for preventing elbow injuries.